Particles in relativistic magnetohydrodynamic jets: ii. bridging jet dynamics with multi-wave band nonthermal emission signatures - Dubey, Ravi; Fendt, Christian; Vaidya, Bhargav (The astrophysical journal, 2024)
Relativistic magnetized jets, originating near black holes, are observed to exhibit substructured flows. In this study, we present synthetic synchrotron-emission signatures for different lines of sight and frequencies, derived from three-dimensional relativistic magnetohydrodynamic simulations of pc-scale Active Galactic Nuclei jets. These simulations apply different injection nozzles, injecting steady, variable, and precessing jets. Extending our previous study, here, we have developed a bridge to connect jet dynamics and particle acceleration within relativistic shocks with nonthermal radiation dominant in jets. The emission is derived from Lagrangian particles—injected into the jet and following the fluid—accelerated through diffusive shock acceleration and subsequently cooled by emitting energy via synchrotron and inverse-Compton processes. Overall, the different shock structures lead to the formation of numerous localized emission patterns—interpreted as jet knots. These knot patterns can fade or flare, also as a consequence of merging or Doppler boosting, leading to jet variability. We find knots with high-enough pattern speed supposed to be visible as superluminal motion ≲5c. Synchrotron spectra of all jets reveal double-humped structures, reflecting multiple electron populations characterized by the nature of underlying shock and their age. The precessing jet is the most powerful emitter, featuring a spectrum flatter than the steady and the variable jet. The emission, although essentially governed by the acceleration through shocks, depends on the cooling history of the particle as well. Overall, the continuous reacceleration of electrons through shocks along the jet we found is an essential prerequisite for observing extended jet emission over large timescales and length scales.
Gesehen am 16.05.2025